Role of Toll-like receptors in costimulating cytotoxic T cell responses. - Schwarz, K; Storni, T; Manolova, V; Didierlaurent, A; Sirard, J; Röthlisberger, P; Bachmann, M (2003)
Stimulation of Toll-like receptors (TLR) by pathogen-derived compounds leads to activation of APC, facilitating the induction of protective immunity. This phenomenon is the basis of most adjuvant formulations currently in development. Here, we tested the ability of TLR2, 3, 4, 5, 7 and 9 signaling to enhance CTL responses upon vaccination with virus-like particles. Stimulation of TLR2 and 4 failed to increase CTL responses, whereas ligands for TLR3, 5 and 7 exhibited moderate adjuvant function. In contrast, stimulation of TLR9 dramatically increased CTL responses, indicating that ligands for TLR9 are likely to be the most promising candidates for the development of novel adjuvant formulations for stimulating CTL responses.